(untitled) (Journal of Computational Mathematics, 2002)
The main purpose of this paper is to present some convergence results for algebraically stable Runge-Kutta methods applied to some classes of one- and two-parameter multiply-stiff singular perturbation problems whose stiffness is caused by small parameters and some other factors. A numerical example confirms our results.